Virtual communities and innovation: proposals from the technical pedagogical advisory in telesecondary school - Bonilla Santamaría, Karen; Ferra Torres, Gerson Edgar (IE Revista de Investigación Educativa de la REDIECH, 2021)
The function of the pedagogical technical advisory in the Telesecondary modality in Mexico is a field of study quite little explored, especially if we add the component of Information Technology, Communication, Knowledge and Digital Learning (ITCKDL). In this article, the results of an innovation proposal are shown within the framework of the Master’s degree in Innovation in Basic Education (MIBE) of the Benemérita Escuela Normal Veracruzana “Enrique C. Rébsamen” in Xalapa, Veracruz, Mexico. Based on the action-research methodology, a diagnosis and assessment of the relevance of the technical-pedagogical accompaniment in a school zone of federal telesecondary schools was carried out through the implementation and monitoring of a virtual learning community (VLC), in which the collaborative work took shape in the design of didactic situations with a view of strengthening the teaching intervention in the classrooms.